Theoretical examination of channel estimation method for TS-OFDM signal under symbol timing offset - Pongsathorn Reangsuntea; Pisit Boonsrimuang; Kousuke Sanada; Kazuo Mori; Hideo Kobayashi (My University, 2016)
Recently the channel estimation method of using a time domain Training Signal (TS) for the Orthogonal Frequency Division Multiplexing (TS-OFDM) has been considered actively by many researchers as an alternative method of using pilot signals in the frequency domain. However most of them were investigated assuming the ideal symbol timing. This paper conducts the theoretical examinations for the effect of channel estimation method of using the TS method when the detected symbol timing has an offset from the ideal symbol timing. This paper also verifies the theoretical analysis by computer simulation results.
Keywords: Symbol (formal); SIGNAL (programming language); Symbol rate; Advanced Wireless Communication Techniques